Pendampingan Wirausaha Jamu Seduh Tradisional melalui Diversifikasi Produk dan Pemasaran Digital - Zahroh, Kavita Faizatus (LPPPM STAI Darul Hikmah Bangkalan, 2021)
The economic sector is no less worse off than theHealth sector in terms of the impact of the Covid-19 pandemic. The implementation of social distancing, Large-Scale Social Restrictions (PSBB), to the Implementation of Community Activity Restrictions (PPKM) with various regulations have made the community's economy worse off. One of the latest regulations is business operating hours. One of the entrepreneurs is Mrs. Sunarsih, who is an entrepreneur of Traditional Herbal Medicine. This is due to a decrease in revenue due to operational congestion. Conventional stores that were originally open from 16.00 to 22.00 must close less than 20.00. The decline in income has also greatly impacted the community's economy, apart from basic needs that have not decreased, there are also other factors that it has, such as health costs so that the body is not susceptible to disease during a pandemic. Therefore, this service aims to help Mrs. Sunarsih to provide innovation to businesses so that they can survive during this pandemic. The method used in this service is mentoring which contains training regarding digital products and marketing. After this service was carried out, Mrs. Sunarsih's income increased thanks to the addition of products made by Mrs. Sunarsih herself, the business has social media that is still developing as a digital marketing medium in addition to conventional marketing in stores, and Mrs. Sunarsih can find out how to determine product prices.